104 Risk Stratification in Acute Coronary Syndrome: Do We Need to Move Beyond Grace?. (3rd June 2016) - Krishnathasan, Kaushiga; Debney, Michael T; Yeung, Chit Sum Jason; Bakhai, Ameet; Lockie, Tim
Abstract : Introduction: The GRACE score predicts in-hospital mortality and is a key tool in the risk stratification of patients with non ST-elevation acute coronary syndrome (ACS). This then determines treatment and the timing of any intervention such as PCI (1). We developed an ACS pathway based on these guidelines incorporating the GRACE score, serial troponin, ECG changes and presenting symptoms in order to categorise patients into high, intermediate and low risk (Figure 1 ). Methods: Based on discharge summary coding all NSTE-ACS patients were selected who presented between Aug 2014 and Jan 2015 at Barnet Hospital, a (non-PCI) district general. Notes were reviewed and GRACE score and risk stratification re-calculated retrospectively using the new pathway. Patient demographics, time to intervention, length of stay and outcome were also collected. Only patients with type 1 ACS were included in the analysis. Data presented as mean +/- SD. Results: 113 ACS patients were admitted during this period. 41(36%) were deemed to be high risk, 43(38%) intermediate risk and 8(7%) low risk. The remaining individuals had insufficient data. In the high risk group, 18(43.9%) were managed conservatively, 17(41.5%) transferred for early invasive management with view for PCI and 6(14.6%) underwent diagnostic angiogram on site. Of those high-risk patients managed invasively, only 4(23.5%) received treatment within <24 h as recommended by the guidelines; 7(29.1%) waited >72 h. In the intermediate risk group 33(76.7%) were managed invasively, including 17(39.5%) <24 h; no patients in this group were managed conservatively. In the high-risk group age 81 ± 11 vs. 64 ± 13 year in the intermediate group (p < 0.001). There was no differences in age between the intermediate and low-risk groups. Creatinine and length of stay were higher in the high risk group compared to the low and intermediate risk groups combined p < 0.05 and p < 0.02 respectively (Table 1 /Figure 2 ). Conclusions: The GRACE score is used to determine timing of PCI in the latest ACS management guidelines. Age of the patient weighs heavily in calculating the score. We found that in a real-world ACS population patients classified as high-risk were on average 20 years older than those in lower risk. They were also frailer, and because of co-morbidities were more likely to wait longer for their PCI, or be managed conservatively. With such an age-related bias, this questions how the GRACE score should be used in management pathways when a high proportion of patients do not qualify for the recommended treatment options. Perhaps other tools are needed for the categorisation of ACS patients to identify the true high-risk population who benefit from early intervention; or inclusion of a frailty index to reflect the complex needs of an increasingly elderly population?